Co-identifying alternative technological innovations for prioritized value chains for the Mbire and Murehwe districts of Zimbabwe - Chimonyo, Vimbayi G. P.; Sibanda, Telma; Matangi, Dorcas; Gadzirayi, Christopher; BIO-HUB Trust (CGIAR, 2023)
The main objective of this action was to co-identify technological and institutional innovations that can be implemented within the agroecology living landscapes (ALLs) to facilitate the agroecological transition with specific reference to pre-selected value chains. The action also aimed to co-develop the action to be implemented in the ALLs by the farmers. This co-development capacitated all stakeholders and built confidence to use local resources to solve local problems. This was done through ALLs thematic working groups, which produced detailed information on quantities and protocols to be used for the application of local technologies within pre-selected value chains. Plenary sessions were held to validate various innovative technologies and to come up with the desired action plans for the 2023/24 farming season. Detailed quantities of various ingredients and protocols for the various local technologies were discussed and validated. Discussions recommended the use of local resources that are less expensive and readily available and further research on technologies that were not validated with little evidence. For the future sustainability of the ALLs, we recommend the development of a Local Farmer Innovation Guide/Manual as a reference for future farming activities.